From rarity to reality: the hidden abundance of critically endangered deep-sea little gulper shark (Centrophorus uyato) in the southern Adriatic Sea - GAJIĆ A. , ANDREJ; SULIKOWSKI A. , JAMES (Mediterranean Marine Science, 2024)
The little gulper shark, Centrophorus uyato (Rafinesque, 1810), is a critically endangered and poorly known deep-sea shark that is considered very rare in certain parts of the Mediterranean, particularly the Adriatic Sea. Between June and August 2023, a total of 47 individuals (25 females and 22 males) were documented 3 to 4.5 NM off Grama Bay in Vlorë, Albania, at depths ranging from 400 to 450 meters. All the recorded individuals were adults, measuring in average 90.53 cm total length and weighting 4.26 kg. Detailed examinations were performed on 10 individuals (5 males and 5 females), while the remaining specimens were retained by fishermen and subsequently sold for consumption. Local ecological knowledge revealed a consistent presence of the species in the longline catches in the studied area. The findings presented in the current manuscript indicate that the species may be more common in the southernmost Adriatic Sea than previously thought. Moreover, data herein support the postulation that the species prefer submarine canyons within the upper slopes.